PEMBERDAYAAN MAHASISWA DALAM PENERAPAN PRINSIP PENGELOLAAN SAMPAH MENGGUNAKAN POLA 4R - Muhsinah Annisa; Fadhlan Muchlas Abrori; Listiani Listiani (LENSA (Lentera Sains): Jurnal Pendidikan IPA, 2018)
Waste is very serious problem, especially in the Tarakan area. One of the ways to manage waste is through empowering the young generation in 4R-based waste managing (reduce, reuse, recycle and replace). This study uses a quantitative descriptive approach through the type of pre-experiment. This study measures the knowledge, skills and attitudes of students in Department of Elementary Teacher School in University of Borneo Tarakan. The pre-experiment research design carried out was one pretest-posttest group on observing student knowledge, and one shot case study on observing skills and attitudes. aspects of knowledge obtained an average before the activity of 50,625 and the average after activity amounted to 79,13889. On the skill aspect, the results obtained on a 1-5 Likert scale on a reduce of 4.5; reuse of 4.25; recycle 4.12; and replace 3.98. The attitude aspect was obtained at 80% in affective, and 76.5% in conative.